What is the role of circRNAs in the pathogenesis of cervical cancer? A systematic literature review - Matos, Ana Gabrielly de Melo; Silva, Gyl Eanes Barros; Barbosa, Eldevan da Silva; de Andrade, Marcelo Souza; Santos Lages, Joyce; Corrêa, Rita da Graça Carvalhal Frazão; Oliveira, Ana Gabriela Caldas; Teixeira, Eliel Barbosa; da Silva, Marcelli Geisse de Oliveira Prata; Fonseca, Susanne Suely Santos da; Teixeira-Júnior, Antonio Augusto Lima; Alves, Matheus Silva; et al. (Frontiers in Genetics, 2024)
Cervical Cancer (CC) is one of the most prevalent neoplasms among women, considered the leading cause of gynecological death worldwide, and the fourth most common type of cancer. Regional metastasis is closely related to the low effectiveness of treatment, and validating biomarkers can optimize accuracy in diagnosis and prognosis. Among the potential biomarkers associated with disease metastasis are circular RNAs (circRNAs), whose altered expression has been linked to CC progression. In this context, this systematic review aims to compile information on the clinical-pathological significance and describe the biological function of circRNAs. Inclusion and exclusion criteria were used to include relevant literature, followed by in silico analysis. Additionally, we employed the UALCAN tools to search for host genes of circRNAs and expression data, miRTargetLink 2.0 to predict interactions of microRNA target genes and the Cytoscape software to predict possible interactions of microRNA target genes. According to the research, most circRNAs were found to be overexpressed and described as regulators of processes such as invasion, cell proliferation, apoptosis and migration. They were also implicated in clinical significance, including metastasis, TNM staging and microRNA interactions. CircRNAs may participate in critical processes in tumorigenesis; therefore, understanding the underlying molecular mechanisms of gene regulation in CC can contribute to the accuracy of diagnosis, prognosis and therapy.